Risk Aversion, time preference, and the social cost of carbon - David Anthoff; Richard S. J. Tol; Gary W. Yohe (The Economic and Social Research Institute (ESRI), 2008)
The Stern Review reported a social cost of carbon of over 300/tC, calling for ambitious climate policy. We here conduct a systematic sensitivity analysis of this result on two crucial parameters: the rate of pure time preference, and the rate of risk aversion. We show that the social cost of carbon lies anywhere in between 0 and 120,000/tC. However, if we restrict these two parameters to match observed behavior, an expected social cost of carbon of 60/tC results. If we correct this estimate for income differences across the world, the social cost of carbon rises to over 200/tC.
Keywords: 330; Klimaschutz; Luftverunreinigung; Kohlendioxid; Soziale Kosten; Zeitpräferenz; Risikoaversion; OECD-Staaten